ChemInform Abstract: Kinetic Resolution in the [2 + 2] Cycloaddition of Ketenes: An Experimental and Theoretical Study. Issue 29 (July 2015) - Rulliere, Pauline; Carret, Sebastien; Milet, Anne; Poisson, Jean‐Francois
Abstract The procedure uses the high difference in reactivity and thus allows the access to pure (E) alkenes, often difficult or impossible to isolate from the mixtures or expensive in trade.